Interfaces de um retrato : identidade e representações do gay/homem em Madame Satã - Lima, André Ricardo Pinheiro (2011)
For centuries, the theme of "sex" was subject to certain constraints. Only in the 1960s, feminist movements have made possible a new look at the gender issue, calling into question the way we are trained and produced as a "gendered subject". Trevisan (1998, p. 190) asserts that there was "the collapse of walls raised to protect certain type of masculinity defined and maintained as such, the iron and fire." Emerged the gay movement, particularly objecting to the requirement of the sexual relationship of men to women exclusively and necessarily, defending a new look at the social body to homoerotic relations. Through these movements, the twenty-first century saw a new gay identity. If before the gay subjects need to imitate women to attract men, nowadays, we witnessed the emergence of more gay men. These new subjects designed to conquer even more male fans. Therefore, in light of the precepts of AD French, a Foucaultian perspective, we try to analyze the discursive marks emanating from the film narrative Madame Satã that contributes to the emergence and subsequent promotion of a gay man, devoid of mannerisms and affectations that characterized gays of old. From the principle that the cinema is a vehicle (re) producing effects of real / reality and facilitating the functioning of (a) normalization of the subjects and their practices, we consider Madame Satã as landmark in the formation of gay identity in Brazil, in the social perspective or in the view of the subject himself. Therefore, the search for determining the emergence of the discourse of a subject politically and socially oppressed who, yearning for a place in the social core, asserts himself as a subject in the world.